Ultrasound diagnosis of emergency conditions of the abdominal cavity with different localization of pain - N. G. Zaviyalova; V. D. Zavadovskaya (Бюллетень сибирской медицины)
This publication shows the comparative capabilities of localized and advanced volume ultrasound in emergency conditions of the abdominal cavity. To achieve this goal, a retrospective analysis of ultrasound examination of 130 patients with OAB in LOAC — 46, NCP — 33, LVK — 14, LNC — 18. The sensitivity of the localized and extended survey of the composition, respectively, in the AHC -81% and 93%, OMV — 33% and 77%, LVK — 50% and 86%, LNC — 53% and 73%. Comparison of the sensitivity of ultrasound examination, depending on the localization of SAR and sonography showed an increased volume of ultrasound can improve the sensitivity of the examination in patients with acute pathology of abdominal organs from 12 to 44%.